Effect of pre-treatments on the antioxidant potential of phenolic extracts from barley malt rootlets. (15th November 2018) - Budaraju, Sravanthi; Mallikarjunan, Kumar; Annor, George; Schoenfuss, Tonya; Raun, Roger
Highlights: Application of autoclave and microwave increased the free phenolic content. BMR extracts obtained by autoclave and microwave had higher antioxidant activity. Pre-treatments did not show significant effect on bound phenolic extracts. Abstract: In this study, barley malt rootlets (BMR) were subjected to five different pre-treatments (steaming (220 °C), roasting (60 °C), autoclaving (121 °C), microwaving (160–800 W, 30–120 s) and enzyme treatment). Total phenolic content (TPC) and antioxidant activity of the BMR extracts were evaluated for both free and bound phenolics. The free phenolic content for non-treated extract was 1.8 mg/g of dry weight of BMR with 17.5% of antioxidant activity. Among the pre-treatments, autoclaving exhibited the highest values for free phenolics of 3.8 mg/g of dry weight of BMR and 71.6% of antioxidant activity. Pre-treatments did not show any effect on bound phenolic content, but increased antioxidant activity. The highest %DPPH activity for bound phenolics was observed for microwave treatment (160 W, 120 s) with 49.9%. Overall, pre-treatments significantly increased the free phenolic content of BMR phenolic extracts. Additional research is necessary to understand the phenolic profile and the thermal interactions of bound phenolic extracts.